Digital Learning Management Systems for Maritime Decarbonization Training: An Adaptive Framework for Seafarer Competency Development - Tri Kismantoro; Ronald Simanjuntak; Muhammad Nurdin; Nafi Almuzani; Ardiansyah, Ardiansyah (Yayasan Literasi Sains Indonesia, 2025)
The International Maritime Organization's 2023 Greenhouse Gas Strategy necessitates rapid workforce transformation to train 1.2 million seafarers in decarbonization competencies by 2050. This qualitative research investigates adaptive digital learning management systems for maritime decarbonization training through analysis of perspectives from five maritime education professionals with specialized expertise in green shipping technologies and IMO-based learning frameworks. The study employs descriptive analysis to examine participant insights regarding intelligent tutoring systems, predictive learning models, and digital assessment frameworks. Results demonstrate strong support for adaptive learning implementation, with an overall effectiveness score of 4.2 out of 5.0 and projected competency development improvements of 63.0% across domains. Thematic analysis reveals five critical dimensions: personalization imperative, real-time assessment integration, scalability solutions, implementation complexity, and regulatory alignment confidence. Adaptive learning systems can potentially train 240,000 seafarers annually compared to 2,400 through traditional methods while maintaining regulatory compliance. Findings contribute to adaptive learning theory and provide implications for maritime institutions.